2015
DOI: 10.3390/molecules20034337
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability Enhancement of Paclitaxel via a Novel Oral Drug Delivery System: Paclitaxel-Loaded Glycyrrhizic Acid Micelles

Abstract: Paclitaxel (PTX, taxol), a classical antitumor drug against a wide range of tumors, shows poor oral bioavailability. In order to improve the oral bioavailability of PTX, glycyrrhizic acid (GA) was used as the carrier in this study. This was the first report on the preparation, characterization and the pharmacokinetic study in rats of PTX-loaded GA micelles The PTX-loaded micelles, prepared with ultrasonic dispersion method, displayed small particle sizes and spherical shapes. Differential scanning calorimeter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(51 citation statements)
references
References 45 publications
2
48
0
1
Order By: Relevance
“…GA has been reported to have an influence on drug permeation in the skin (Sapra et al, 2008), and it has also been studied as a paclitaxel micelle carrier in our research group (Yang et al, 2015). In the present study, GA's solubilization property improved the solubility of POD and the formulation could reach a concentration of 5 mg/mL.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…GA has been reported to have an influence on drug permeation in the skin (Sapra et al, 2008), and it has also been studied as a paclitaxel micelle carrier in our research group (Yang et al, 2015). In the present study, GA's solubilization property improved the solubility of POD and the formulation could reach a concentration of 5 mg/mL.…”
Section: Discussionmentioning
confidence: 49%
“…The preparation of the POD-loaded GA micelles followed the ultrasonic dispersion method (Yang et al, 2015). GA was dissolved in preheated distilled water, and a solution of POD in ethanol was added (the weight ratio of POD: GA was 1:8) dropwise into the preheated aqueous GA solution at 60 C. The resulting solutions contained 5 mg/mL POD, 40 mg/mL GA, and 25% (v/v) ethanol.…”
Section: Preparation Of the Pod-loaded Ga Micellesmentioning
confidence: 99%
“…SMA-PTX micelles showed comparable IC 50 values as compared to the free PTX and PTX (Ebewe) in CT-26.luc colon cancer cells. Furthermore, the SMA copolymer did not affect the cell viability at the mentioned concentrations, which is in agreement with the previous study 41 and supports the inert nature of SMA copolymer previously described.…”
mentioning
confidence: 87%
“…49 However, Abraxane, which is an albumin-bound PTX nanoformulation, shows instability in the GI tract 50 and thus is unfavorable for oral administration. Other oral PTX formulations, such as BMS-275183, in a Phase I clinical trial showed grade 1 and grade 2 liver-associated toxicity 51 in four out of 20 patients with nonhematologic malignancy, when administered with an oral dose of 6 mg/m 2 /d of BMS-275183.…”
mentioning
confidence: 99%
“…1,2 It has a significant clinical application for which it is in the World Health Organization's List of Essential Medicines but oral bioavailability of this drug is disgustingly limited by poor water solubility, P-gp efflux and CYP3A metabolism. [3][4][5] Currently, it is administered through intravenous route that is also related to some clinical compromises due to the side effect of used formulation excipients. Several research activities are going on to counteract these situations through different formulation approaches.…”
Section: Introductionmentioning
confidence: 99%